"Chromium Volatilization and Oxidation of Ferritic Steels Used as Interconnects in Solid Oxide Fuel Cells" - Ravash, Hamed (My University, 2010)
Cr evaporation of the metallic interconnects and the resulting poisoning of the cathode continues to be one of the main degradation problems for SOFCs. A large number of ferritic steels have been used as interconnect materials. While some of the materials have been developed for SOFC purposes recently others have been produced on a large scale for many years. A number of commercial products (e.g. Crofer 22 APU, Crofer 22 H, Sanergy HT, ZMG 232) are exposed at 850°C to a humidified air at high flow rate. Cr evaporation is measured by a novel denuder technique where Na2CO3 is used to getter volatile Cr (VI) species. The amount of chromium is quantified in a time resolved manner by photo spectroscopy. Effects of different parameters like SOFC working temperature, gas velocity and plastic deformation on Cr evaporation from metallic interconnects are investigated. It is unlikely that uncoated ferritic steels will provide good long-term SOFC performance. However, thin film coatings can be used in order to enhance surface properties for SOFC applications achieving e.g. increased oxidation resistance, higher electronic conductivity or improved Cr retention. The latter is especially important since the Cr-Mn spinel formed by most of the commercially available interconnect materials does not provide sufficient Cr retention. The present results show that Cr evaporation can be strongly reduced by submicron Co coatings that are deposited in a cost efficient way in a roll to roll process. The compound scales formed after oxidation at high temperature are investigated with TEM, SEM/EDX, and XRD.
Keywords: Kemi; Chemical Sciences